The effect of different strength training modalities on sprint performance in female team-sport athletes: a systematic review and meta-analysis - Hughes, W.; Healy, R.; Lyons, M.; Nevill, A.; Higginbotham, C.; Lane, A.; Beattie, K. (Sports Medicine, 2023)
Background: There has been a rise in the participation, professionalism, and profile of female sports in recent years. Sprinting ability is an important quality for successful athletic performance in many female team sports. However, much of the research to date on improving sprint performance in team sports is derived from studies with male participants. Given the biological differences between the sexes, this may be problematic for practitioners when programming to enhance sprint performance in female team-sport athletes. Therefore, the aims of this systematic review were to investigate (1) the overall effect of lower body strength training on sprint performance, and (2) the effect of specific strength training modalities (i.e., reactive-; maximal-; combined-; special-strength) on sprint performance in female team-sport athletes. Methods: An electronic database search was performed using PubMed, MEDLINE, SPORTDiscus, CINAHL, The Cochrane Library, and SCOPUS to identify relevant articles. A random-effects meta-analysis was performed to establish standardised mean difference with 95% confidence intervals and the magnitude and direction of the effect. Results: Fifteen studies were included in the final analysis. The 15 studies represent a total sample size of 362 participants (intervention n = 190; control n = 172) comprising 17 intervention groups and 15 control groups. The overall effects revealed small improvements in sprint performance in favour of the experimental group over 0-10 m and moderate improvements over sprint distances of 0-20 m and 0-40 m. The magnitude of improvement in sprint performance was influenced by the strength modality (i.e., reactive-, maximal-, combined-, and special-strength) utilised in the intervention. Reactive- and combined-strength training methods had a greater effect than maximal- or special-strength modalities on sprint performance. Conclusion: This systematic review and meta-analysis demonstrated that, when compared with a control group (i.e., technical and tactical training), the different strength training modalities exhibited small to moderate improvements in sprint performance in female team-sport athletes. The results of a moderator analysis demonstrated that youth athletes (< 18 years) yielded a greater improvement in sprint performance compared with adults (= 18 years). This analysis also supports the use of a longer programme duration (> 8 weeks) with a higher total number of training sessions (> 12 sessions) to improve overall sprint performance. These results will serve to guide practitioners when programming to enhance sprint performance in female team-sport athletes.